Метричний запис про народження та хрещення Михайла Петровича Старицького (до 180-річчя з дня народження) - Кравцов, А. (Сiверянський лiтопис, 2019)
Статтю присвячено пошуку оригінальних документів про дату народження
Михайла Петровича Старицького. Розглядаються можливі місця зберігання такої
інформації. Аналізуються причини та джерела впровадження у науковий обіг помилкової дати. Публікується виявлений документ із виписом з метричної книги про народження Михайла Старицького. This article is about birth record of Mykhailo P. Starytsky. He was a famous Ukrainian
writer, poet, and playwright.
Nowadays, there is a generally accepted version of Mykhailo Staritsky’s birth date. It is
14 (2 Old Style (O.S.) December 1840. Nevertheless, this version is not confirmed by original
sources. The original sources were lost in 1943, when the state archive of the Poltava region
and its Kremenchuk branch lost all their documents including metrical books with birth record
of Mykhailo Starytsky. Because Mykhailo Starytsky was born in nobility family, we may
attract additional sources. The author verifies others documents, such as Vadim Modzalevskyj’s
«Malorossyjskyj rodoslovnyk» and finds another date. That date is 14 (2 O.S.) November 1839.
Further, the author searches original source of this information in fond «Third Department
of Senate» (Department of Geroldii) of Russian State Historical Archive, St. Petersburg. In
result, the author finds the copy of extract of birth record of Mykhailo P. Starytsky, which
confirm date 14 November 1839.
Additionally, the paper deals with finding the source of wrong date (14 December 1840).
The author traces a sequence of links to sources in publications about Staritsky and finds
the possible first article with wrong date. This article was published in 1940, but its author
Luka Sokyrko did not point the source of date. Therefore, we cannot set source of wrong date.
On completion, the article shows analyzing of information from found extract of birth
record. The author publishes full text of this document saving authentic language specifics.